Biomimetic mineralization of hydroxyapatite crystals on the copolymers of vinylphosphonic acid and 4-vinilyimidazole - Dogan, Ozlem; Oner, Mualla (AMER CHEMICAL SOC, 2006)
In the present work, copolymers of vinylphosphonic acid and 4-vinilyimidazole (poly(4-VIm-co-VPA)) were found to be substrates favoring the precipitation of nanohydroxyapatite (HAP) crystals from stable supersaturated solutions at pH 7.4 and 37 degrees C. Deposition kinetics were studied by the constant composition technique. The rates of crystallization both on HAP seed crystals as reference and on the copolymer in powder form were investigated at constant supersaturation conditions. The rates of HAP crystal growth on the polymeric substrate were found to depend on the amount of seed material and on the phosphate content of the copolymer.
Keywords: CALCIUM PHOSPHATES; IN-VITRO; CRYSTALLIZATION; GROWTH; POLYELECTROLYTES; BIOMINERALIZATION; CALCIFICATION; INHIBITION; POLYMERS; ZINC; Chemistry; Materials Science